Picosecond laser surface micro-texturing for the modification of aerodynamic and dust distribution characteristics in a multi-cyclone system. Issue 1 (31st December 2016) - Otanocha, Omonigho B.; Lin, Li; Zhou, Yuanye; Zhong, Shan; Zhu, Liu
Abstract: Aerodynamic flow control in a cyclone is critical to its performance. Dust accumulation in a multi-cyclone is undesirable. This research investigated, the effects of laser-patterned Ethylene-Propylene-Diene Monomer (EPDM) roof in a commercial multi-cyclone system on its aerodynamic and dust accumulation characteristics. Our experimental data show that strategically designed concentric micro-dimples on the cyclone roof can improve both the aerodynamic performance and dust separation capability in the multi-cyclone system. With specific laser-patterned cyclone roof, up to 78% reduction in dust adhesion was demonstrated in one of the cones (cone 9). With the 315-μm diameter micro-dimples on EPDM roof, it was observed that dimples located close to the vortex finder caused an increase in the reverse airflows in the cyclone, thereby effecting entrainment of dust. The overall dust separation efficiency of the multi-cyclone system was at an average of 99.9% with the laser-textured roof, hence no adverse effect on the original cyclone system, in spite of the reported improvements in dust adhesion reduction.